Analisis Kebutuhan Media untuk Pengembangan E-Book Tema Abrasi pada Pembelajaran Fisika Era 4.0 - Azmanita, Yuni; Festiyed, Festiyed (Universitas Negeri Padang, 2019)
The era of the industrial revolution 4.0 is very possible for information systems to be able to convert the printed form to electronic form. These advantages can be used to develop an e-book as a media in learning Physics. This e-book is an ICT-based electronic media that can be used as a learning media. The purpose of this study is to describe the results of an analysis of media needs in schools, as a stage of initial investigation in the development of an e-book with the theme of coastal abrasion. This research used a descriptive method. The research subjects were the population of the students of SMAN 1 UlakanTapakis with the sample selected using a simple random sampling technique. The data from this study are primary data obtained through a questionnaire with data collection techniques using the Likert scale 1-4. The data analysis technique is in the form of descriptive statistics. The results of the analysis of media needs obtained an average percentage of 45.02% which was included in the category of lacking. On the other hand, the issue of coastal abrasion needs to be considered especially for students who live on the coast. For this reason, an instructional media in the form of an integrated abrasion beach is needed